DEIKSIS DALAM FILM CINDERELLA: ANALISIS PRAGMATIK - MERENTEK, SILVIA HARIYATI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT In English, there are 5 types of deixis, those are: person deixis (1st person deixis, 2nd person deixis and 3rd person deixis), place deixis, time deixis, discourse deixis, and social deixis. Deixis itself is a pointing term in language. This study is an attempt to describe and analyze deixis which is found in the film Cinderella. The aim of this research is to identify and classify the form and the meaning of deixis used in the film. The method used in this research is descriptive method. The data of deixis have been taken from the sentences in the film Cinderella and analyzed using Levinson’s concept. The result of this study shows that deixis is classified into 5 forms, those are: person deixis (1st person deixis: I, my; 2nd person deixis: you, your; and 3rd person deixis: they, her, she, he him), place deixis: inside, away, behind, here, besides, there, here; time deixis: now, two weeks hence; discourse deixis: that, it; and social deixis: madam, miss, mister, Your Royal Highness, Your Majesty, prince. —————————————————————- Keywords: deixis, , Pragmatic Analysis, Film Cinderella